Connected for development - "Badshah,Akhtar(ed.)" (New York, 2005)
The digital divide is a significant component of the development divide and that ICT can be a factor in responding to the new challenges of globalisation and addressing longstanding issues of inequality. However the evidence is that top-down initiatives never work unless they are fully endorsed at local level. This book is a resource to help the spread of community access points. It covers five themes: enabling an environment for the development of information kiosks; characteristics of success; measuring impact; new approaches to ICT for development; selected case studies.
Keywords: Economic development